Ionic liquids as solvents to separate the azeotropic mixture hexane/ethanol - Sandra Corderí (2013)
In this work the imidazolium ionic liquids 1-hexyl-3-methylimidazolium trifluoromethanesulfonate, [HMim][TfO], 1-hexyl-3-methylimidazolium dicyanamide, [HMim][N(CN)2], 1-hexyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, [HMim][NTf2], and 1-methyl-3-propylimidazolium bis(trifluoromethylsulfonyl)imide, [PMim][NTf2], were studied as solvents for the separation of ethanol from its azeotropic mixture with hexane. The liquid-liquid equilibrium (LLE) of the ternary systems {hexane + ethanol + [HMim][TfO], or [HMim][N(CN)2], or [HMim][NTf2], or [PMim][NTf2]} was carried out at 298.15 K and atmospheric pressure. From the experimental LLE data, the solute distribution ratio and selectivity were calculated and the solvent capacity of the studied ionic liquids was compared with another ionic liquid from literature. Finally, the experimental LLE data were correlated using the NRTL and UNIQUAC thermodynamic models.